COMMUNITY AFFECT DAN BRAND COMMUNITY TRUST TERHADAP BRAND EQUITY - Yuraldi Mahaprasasta (Ekonomi Bisnis, 2017)
Abstact : The research aims to examine and analyze the influence of Brand Community Affect and Brand Community Trust to the brand equity, and examined the effect of brand community affect and brand community trust on brand equity through brand loyalty. This research’s object is all active members of the Yaris Club Malang as many as 73 people. The sampling technique used is total sampling method. The collected data analyzed using the analysis of PLS (Partial Least Square). Research results obtained are Brand Community Affect has a positive significant effect on brand equity directly; Brand Community Trust has a positive significant effect on brand equity directly; Brand Community Affect has a positive significant effect on brand loyalty directly; brand community trust has a positive significant effect on brand loyalty directly; brand loyalty has a positive significant effect on brand equity directly; Brand community affect has a positive significant effect on brand equity through brand loyalty, brand community trust has a positive significant effect on brand equity through brand loyalty. Keywords  : Brand Community Affect, Brand Community Trust, Brand Equity, Brand Loyalty Abstrak : Penelitian ini bertujuan untuk menguji dan menganalisis pengaruh brand community affect dan brand community trust terhadap brand equity, serta menguji pengaruh brand community affect dan brand community trust terhadap brand equity melalui brand loyalty sebagai variable mediasi. Obyek penelitian ini adalah seluruh anggota aktif Malang Yaris Club sebanyak 73 orang. Teknik pengambilan sampel yang digunakan adalah metode total sampling. Teknik analisis data menggunakan analisis PLS (Partial Least Square). Hasil penelitian yang didapatkan adalah Brand Community Affect berpengaruh positif secara langsung terhadap Brand Equity; Brand Community Trust berpengaruh positf secara langsung terhadap Brand Equity; Brand Community Affect berpengaruh positif secara langsung terhadap Brand Loyalty; Brand Community Trust berpengaruh positif secara langsung terhadap Brand Loyalty; Brand loyalty berpengaruh positif secara langsung terhadap Brand  Equity, Brand Community Affect berpengaruh positif terhadap Brand  Equity melalui Brand Loyalty, Brand Community Trust berpengaruh positif terhadap Brand Equity melalui Brand Loyalty.  Kata Kunci : Brand Community Affect, Brand Community Trust, Brand equity, Brand Loyalty.